THE WORK TIME SPENT BY FEMALE RABBIT BREEDERS AND ITS’ INFLUENTIAL FACTORS - S. N. Sirajuddin; St. Rohani; . Kridayanti (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The aim of this research was to find out the work time spent by female rabbit breeders and factors influencing the work time spent to raise rabbits in Soppeng, South Sulawesi. The research used survey method with female rabbit breeders as analysis unit. Population of 356 female rabbit breeders in Soppeng was used and a sample of 78 female rabbit breeders were selected by region. The result of the research showed that average work time of female rabbit breeders was 3.044 hours per day, which was spent cleaning cages and equipment, preparing feedstuffs and feeding on rabbits, assisting bunnies breastfeed to their mother and health care. The F-test results reveal that the most significantly influential factors affecting female rabbit breeders work time was household income, number of dependents, rabbit breeding income, and the level of experience in breeding rabbits.